Deutsche und russische Literatur an der Schwelle zur Moderne "Wilhelm Meisters Lehrjahre" und "Eugen Onegin". Zur Entstehung des modernen Weltbildes - Rybakov, Alexei (Slavistische Beitraege, 2000)
This work originated from a (seemingly) simple question, but at the same time it tries to discuss a general problem. The question is: where does the plot of the "Wilhelm Meister apprenticeship" actually take place? Is it a "real" world, a world that we "know otherwise" or, given the time gap that separates us from this world, we also use other, non-literary, and in any case, non-work, means (for example, with the help of historical research) can open up to us? Can we even speak of a "reality in itself"? Or has she become questionable to us? Or do we only see a - concept in it? The latter is the case for this work.